GE_GERICHTE A/3549/2024 vom 28. Oktober 2024 - GE Cour de justice (2024)
DÉTENTION AUX FINS D'EXPULSION | LEI.75.al1.letb; LEI.75.al1.leth; LEI.76.al1.letb.ch1; LEI.76.al1.letb.ch3; LEI.76.al1.letb.ch4; LEI.80.al3